The Potential Role of Exercise in Neuro-Oncology - Cormie, Prue; Nowak, Anna K.; Chambers, Suzanne K.; Galvão, Daniel A.; Newton, Robert U. (Frontiers in Oncology, 2015)
Patients with brain and other central nervous system cancers experience debilitating physical, cognitive and emotional effects that significantly compromise quality of life. Few efficacious pharmacological strategies or supportive care interventions exist to ameliorate these sequelae and patients report high levels of unmet needs in these areas. There is strong theoretical rationale to suggest exercise may be an effective intervention to aid in the management of neuro-oncological disorders. Clinical research has established the efficacy of appropriate exercise in counteracting physical impairments such as fatigue and functional decline, cognitive impairment as well as psychological effects including depression and anxiety. While there is promise for exercise to enhance physical and psychosocial wellbeing of patients diagnosed with neurologic malignancies, these patients have unique needs and research is urgently required to explore optimal exercise prescription specific to these patients to maximise safety and efficacy. This perspective article is a discussion of potential rehabilitative effects of targeted exercise programs for patients with brain and other central nervous system cancers and highlights future research directions.